2003
DOI: 10.1007/s00068-003-1300-x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Fracture-Dislocation of the Hip in Sports

Abstract: Posterior fracture-dislocation of the hip is a rare injury in sports and is most frequently seen after road traffic accidents. A posterior fracture-dislocation of the hip that occurred in an adult sportsman during rugby is reported. This case illustrates the great forces that can be sustained by the hip joint of rugby players. Operative stabilization led to a stable hip joint allowing early mobilization. Following rehabilitation, the patient returned to light sporting activities after 9 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Letournel and Judet [13] showed that the posterior rim of the acetabulum bears the impact from the femoral head in this leg position. Acetabular fractures from sports are a rare occurrence and cases have often involved the same mechanism of injury as in our case [14,15]. Joint reactive force (JRF) is involved in hip joint biomechanics and represents the sum of the mechanical forces acting across the hip joint.…”
Section: Discussionmentioning
confidence: 96%
“…Letournel and Judet [13] showed that the posterior rim of the acetabulum bears the impact from the femoral head in this leg position. Acetabular fractures from sports are a rare occurrence and cases have often involved the same mechanism of injury as in our case [14,15]. Joint reactive force (JRF) is involved in hip joint biomechanics and represents the sum of the mechanical forces acting across the hip joint.…”
Section: Discussionmentioning
confidence: 96%
“…Epstein also reported much higher rates of traumatic arthritis in these patients. Most authors also agree that associated acetabular fractures treated by open reduction and internal fixation usually have a good to excellent results when anatomic reduction was obtained 3 , 5 , 7. Indications for operative management include articular displacement more than 2 mm, intraarticular fragments, unstable hip after closed reduction, irreducible hip, vascular injuries and ipsilateral femoral fractures 3 , 7…”
Section: Discussionmentioning
confidence: 97%
“…But to our knowledge, there is no case reported that have a pure hip dislocation when playing non-contact sport like tennis. In English literature there are 21 traumatic hip dislocations with and without fracture in sports activity [2][3][4][5][6][7][8]. Among all these -6 rugby, 5 soccer, 2 futsal and one each water skiing, equestrian, gymnastic, jogging, skiing, biking, sledge, basketball player had traumatic hip dislocation-only five of them were pure dislocations.…”
Section: Discussionmentioning
confidence: 99%